Sosialisasi Budidaya Tebu (Saccharum Offocinarum L.) Dengan Bibit Asal Bagal 1 Mata Tunas Di Desa Gintungan Kecamatan Kembangbahu Lamongan - Wiharyanti Nur Lailiyah; Rahmad Jumadi (Universitas Merdeka Surabaya, 2022)
Most of the sugarcane farmers in Gintungan village have not implemented cultivation perfectly. The use of sugarcane seeds is generally taken from the previous cultivation of sugarcane plants and uses a 2-3 bud mule system so that more seeds are needed and the results obtained are classified as very low. Mule seedlings with 3-4 buds usually cannot grow 100% because the position of the buds is not parallel so that there are shoots that are facing the ground and cannot grow properly. Sugarcane cultivation technology that is not yet known by farmers is the use of sugarcane seeds from a single bud mule. Utilization of sugarcane seeds with one bud is considered a very effective and efficient alternative for farmers. By using this type of seed, the need for seeds for sugarcane cultivation is getting less and less.